PENAMBAHAN KULIT BATANG POHON BAWANG HUTAN (Scorodocarpus borneensis Becc) TERHADAP KUALITAS GULA KELAPA - sari wahyuni fitri; Yohana S Kusuma Dewi; dwi raharjo (FoodTech: Jurnal Teknologi Pangan, 2018)
Traditionally, palm sugar was processed by evaporation of sap coconut which was added to stem bark of Vatica leucocarpa. However, now its rarely found, so that the alternative substitute for Vatica leucocarpa with stem bark of wood garlic. The goal of this research was to determine the quality palm sugar that was processed by addition of wood garlic stem bark. The research design was used a randomized block design. The treatments of stem bark concentration were stem bark of wood garlic 1; 2; 3; 4; 5; and 6 g /l of nira, and stem bark of Vatica leucocarpa 3 g/l of nira, each treatments have 4 replications. Characteristics produced of the sap were a pH of 5,15 and the total soluble solid of 16,28obrix. The characteristics of palm sugar include water content (7,42%), ash (1,05%), total acidity (0,07%), total dissolved solids (81,25obrix) and the sensory characteristics include color 3,48 (brown), texture 3,72 (hard) and taste 3,72 (sweet). The result showed that the best quality of palm sugar was produced by addition stem bark of wood garlic 2 gr/l of sap.